RETRACTED: Regulatory frameworks for sustainable entrepreneurship in the arctic: Environmental law and policy in the Russian Federation - Churilov Aleksei (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001